Timing of puberty and school performance: A population-based study - Suutela, Maria; Miettinen, Päivi J.; Kosola, Silja; Rahkonen, Ossi; Varimo, Tero; Tarkkanen, Annika; Hero, Matti; Raivio, Taneli (Frontiers in Endocrinology, 2022)
Objective: To determine whether the timing of puberty associates with school performance. Methods: Growth data on 13,183 children born between 1997 and 2002, were collected from child health clinics and school healthcare and school performance data from school records. Age at peak height velocity (PHV) marked pubertal timing. The relationships between age at PHV and average grades in mathematics, native language, English, and physical education from school years 6 (end of elementary school; age 11-12 years), 7 (start of middle school; 12-13 years), and 9 (end of middle school; 14-15 years) were modeled using generalized estimating equations and linear mixed models, adjusted for the month of birth and annual income and education levels in school catchment areas. Results: The mean (SD) age at PHV was 13.54 (1.17) years in boys and 11.43 (1.18) years in girls. In girls, age at PHV was associated with grades in mathematics (β=0.041–0.062, p<0.005) and physical education (β=0.077–0.107, p<0.001) across the study years, and in school year 9, also with grades in English (β=-0.047, 95%CI -0.072 to -0.021, p<0.001). Among boys, only the grades in physical education were related to age at PHV across the study years (β=0.026–0.073, p<0.01) and in middle school the grades in mathematics decreased dramatically. Conclusions: In both sexes, the timing of puberty was associated with the grades in physical education, and in girls, with academic achievement. The decrease in boys’ mathematics grades and sex difference in academic achievement were unexplained by the timing of puberty.